Competências individuais: secretários executivos das Universidades federais do estado de São Paulo - Raviani, Crysthian Grayce [UNIFESP] (2015)
Increased production and efficiency are issues that have been researched, there are at least 130 years. In the 70s arises Management Skills for this new people management model, the answer to the increased production and efficiency is on skills, they are responsible for the difference between produce and produce more and better. Recognizing the importance of the issue, in 2006, the federal government issued Decree 5707 which elected the Management Skills as the official tool for the training of its human resources management. This research aimed to identify the skills necessary for the work of the Executive Secretaries of Higher Education Federal Institutions (IFES). The research focused on the state of São Paulo, in UFABC universities UFSCar and Unifesp thus the 125 Executive Secretaries who work in these institutions are the people of this research. There was also a need to investigate on what was the stage of implementation of the Management Skills in these three institutions. The research was divided into three stages. The first aimed to identify the profile, tasks and skills that respondents judged necessary to their work so that it would contribute in a meaningful way to achieve the mission of IFES. The second stage was designed to investigate how was the implementation of Management Skills in these three IFES. The third stage dealt with the validation of the twelve most mentioned skills in the first stage. The results showed that, to date, only UFABC implemented the Management Skills and the first twelve skills necessary for the work of the Executive Secretaries who work in IFES, from the point of view of those surveyed are in the order of their citation: Writing, Commitment, Teamwork, Responsibility, Advice, know the institution, Ethics, Portuguese, Interpersonal Relationship, Document Control, Troubleshooting and Cooperation.